Long-term oxygen therapy in precapillary pulmonary hypertension - SOPHA study - Benjamin, Nicola; Echampati, Ishan; Harutyunova, Satenik; Eichstaedt, Christina; Egenlauf, Benjamin; Ulrich Somaini, Silvia; Grünig, Ekkehard; Xanthouli, Panagiota (Scientific reports, 2024)
Current guidelines recommend oxygen (O2) supplementation in patients with pulmonary hypertension (PH), despite scarce data on long-term O2 therapy (LTOT). The aim of this prospective, randomized, controlled trial was to investigate the effect of LTOT in patients with precapillary PH on exercise capacity, clinical parameters and hemodynamics. Patients with precapillary PH under stable therapy and O2 desaturations at rest and/or during exercise were randomized to receive LTOT (≥ 16 h/day) or no O2 (control group) for 12 weeks. The control group was offered LTOT after 12 weeks. The primary endpoint changes of 6-minute walking distance (6MWD) from baseline to 12 weeks was hierarchically tested: (1) pre-post primary and secondary intervention (2) intervention vs. control group. Secondary endpoints included changes in clinical parameters. Twenty patients were randomized (women n = 14, age 67 ± 11.4 years, mean pulmonary arterial pressure 39.7 ± 12.5 mmHg, 70% functional class III). 6MWD significantly improved by 42.2 ± 34.20 m (p = 0.003) within 12 weeks LTOT. The intervention group significantly improved in 6MWD (38.9 ± 33.87 m) compared to the control group (− 12.3 ± 21.83 m, p = 0.015). No consistent between-group differences in other parameters were found. LTOT was well tolerated and led to significant improvement of 6MWD. The effect of LTOT should be investigated in larger controlled-trials.
Online veröffentlicht: 26. September 2024
Gesehen am 14.03.2025